Методологічні аспекти інституціонального забезпечення сталого розвитку територій у контексті процесу децентралізації - Шарий, Г.І.; Обиход, Г.О.; Дубіщев, В.П. (Економіка природокористування і сталий розвиток, 2019)
Визначено напрями інституціоналізації виконавчої влади, розвитку територій відповідно до вимог інституціоналізму, цілей сталого розвитку та їх ролі в адміністративно-територіальній реформі. Доведено, що єдиним дієвим інституціональним комплексом суспільства є інституціональна матриця – стійка тріада базових елементів – макроінститутів, що інтегрують і стабілізують суспільство, а саме економіки, політики і культури. Наголошено, що модернізація системи інститутів державного управління, делегування повноважень на рівень об’єднаних територіальних громад повинні формувати стійку систему сталого розвитку території та безпечне соціо-еколого-економічне середовище. The institutional system in Ukraine, which is characterized by the rule of interests of the authorities over the interests of the society, neglect of the rights of business agents, as well as the use of power for the personal benefit of officials, is investigated. At the same time, the state is the main institution for sustainable development, which should determine the priority economic, social and environmental activities. Responsible institutions are obliged to develop the necessary mechanisms to ensure sustainability, strengthen positions in the areas of human capital development and improve the quality of life. New governance tools and mechanisms will facilitate the involvement of the private sector in the implementation of sustainable development principles through renewed relationships between business entities based on equal partnership and the use of mechanisms to ensure the harmonization of business interests in achieving social, economic and environmental sustainability. Irrationality, disproportionality, complexity of administrative-territorial entities of the united territorial communities were taken into account in this article. Ways of executive power institutionalization, development of territories in accordance with requirements of institutionalism, and its role and place in administrative-territorial reform were determined. It is argued that the only institutional set of society is an institutional matrix. Institutional matrix of society is presented as a stable triad of basic elements – macro-institutions that integrate and stabilize society: economy, politics, and culture. And the modernization of the system of public administration institutions, decentralization of powers to the level of united territorial communities should form a stable system of sustainable development of the territory and a safe socio-ecological and economic environment.